2008
DOI: 10.1016/j.exppara.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in Trypanosoma brucei

Abstract: Trypanosoma brucei-thwarts the host immune response by replacing its variant surface glycoprotein (VSG). The actively transcribed VSG is located in one of ~20 telomeric expression sites (ES). Antigenic variation can occur by transcriptional switching, reciprocal translocations, or duplicative gene conversion events among ES or with the large repertoire of telomeric and nontelomeric VSG. In recently isolated strains, duplicative gene conversion occurs at a high frequency and predominates, but the switching freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
(89 reference statements)
0
14
1
Order By: Relevance
“…In addition, T. brucei telomeres grow by 6–8 bp/PD during growth under laboratory conditions (a process that has only been observed in this organism) [25], [30]. What is distinct between the natural T. brucei lifecycle and their laboratory propagation that could account for the observed differences in telomere lengths?…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, T. brucei telomeres grow by 6–8 bp/PD during growth under laboratory conditions (a process that has only been observed in this organism) [25], [30]. What is distinct between the natural T. brucei lifecycle and their laboratory propagation that could account for the observed differences in telomere lengths?…”
Section: Discussionmentioning
confidence: 88%
“…Thus it has been suggested that when the telomere of the chromosome harboring the active BES is short the DNA breaks precipitating telomeric deletions would occur upstream of the VSG , resulting in an antigenic switch [24]. This claim was further correlated to the fact that strains of T. brucei that have been recently isolated from nature, who switch at a rate of approximately 10 −2 –10 −3 , have shorter telomeres than laboratory-adapted strains, whose rate of switching can be are 100–10,000-times lower [27], [28], [29], [30]. In all, this suggested an inverse correlation between telomere length and the amount antigenic switching in T. brucei [24], yet there were no data in direct support of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to laboratory strains, T. brucei field strains possess shorter telomeres [49], and switch VSGs more frequently [50,51]. A recent study revealed that telomere length is correlated with VSG switching frequency, and demonstrated that the shorter the telomere structure at an active ES, the more frequently VSG switching occurred [52].…”
Section: Transcription In T Bruceimentioning
confidence: 99%
“…The localization of specific histone variants, modified histones [21] and glycosylated thymidines [49] at sites of pol II transcription initiation and termination is striking. Also, ORC1, implicated in the nucleation of a repressive heterochromatin at the silent mating type loci in S. cerevisiae , was shown to be recruited to PTU flanks as well as the silent VSG arrays in T. brucei .…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…In consistence with the hypothesis, several T. brucei strains with only limited propagation in a laboratory (usually called pleomorphic strains) have much higher VSG switching rate (10 -4 to 10 -2 per population doubling) and relatively shorter telomeres (3-12 kb long, with an average of 8-10 kb) (Dreesen & Cross 2008). In contrast, the 427 Lister strain has been extensively propagated in the laboratory, has a VSG switch rate of 10 -6 per generation, and has telomeres ranging 3-20 kb with an average of 15 kb .…”
Section: Telomere Proteins Influence Vsg Switching Frequency In T Brmentioning
confidence: 99%